The Understanding of Hadith “Ballighû ‘annî walau Âyah" in Twitter - Qurrata A'yun; Yor Hananta (Jurnal Ushuluddin, 2020)
So far, in social media, the hadith "ballighū 'annī walau āyah" has been widely misunderstood as a proposition for preaching even if it is only one verse. On the other hand, this hadith is also used as a suggestion for preaching without understanding the full meaning of a verse. This understanding is different from the real understanding, so a comprehensive discussion is needed to describe it. This article aims to identify misconceptions in understanding the hadith "ballighū 'annī walau āyah" on social media twitter and meet them with the correct meanings of the hadith. This study is a qualitative study which classify and analyze data by descriptive analysis. The discussion of this article explains how the hadith ballighū 'annī walau āyah is understood by Twitter netizens. The understanding of netizens is grouped into two categories, namely those that are appropriate and not in accordance with their real understanding. The factors that lead to misunderstanding of the hadith ballighū 'annī walau āyah are the insights of the hadith that are conveyed only a piece (not intact) and the dissemination of understanding through social media twitter with a short number of characters. This phenomenon causes a transformation of the hadith understanding in the form of degradation and distortion